Magnetic anomalies and the features of geodynamic development of the Antarctic Peninsula continental margin structures - V.D. Soloviev; I.N. Korchagin (Геофизический журнал, 2017)
New geophysical models of the Earth's crust were used to study the possible nature of the Pacific Margin Anomaly (PMA) near the Antarctic Peninsula (AP). The data have been presented, which permitted analyzing spatial distribution of PMA and its deep sources on the continental margin of AP. Western and Eastern PMA-branches may correspond to different crustal blocks associated with predominantly Cretaceous magmatic intrusions of basic rocks. These branches of PMA were formed in the Early Cretaceous in structures, separated by a fault zone. Spatial heterogeneity of different segments of РМА may also be connected with different depth, thickness and magnetic susceptibility of separate bodies, which form the sources of regional anomalies. Active tectonic processes in the Mesozoic—Cenozoic resulted in the complex evolution of the structures of the region and appearance of vast deep magnetic sources of PMA along the AP margin formed during the phases of magmatic activity. Formation of separate segments of PMA can be connected with processes of tectonic movements near the border of the plates (Antarctica and Scotia) as well as in the areas of paleorifts formation. New geophysical results for different PMA-segments (from the Palmer Land to Powell Basin) replenish current ideas on the sources and origin of this big positive magnetic anomaly of the Pacific coast and show the necessity of searching new mechanisms of forming the structures of continental margin of AP